The effects of continuing professional education on the upward career mobility of health services administrators - Richard Brown; Peter Easton (Adult Education Research Conference, 1994)
This study brings quantitative and qualitative data to bear on investigation of the relationship between the participation of health care administrators in formal and informal types of continuing professional education and their upward career mobility.